Coal industry in the context of Ukraine economic security - Mamaikin, O.; Kicki, J.; Salli, S.; Horbatova, V. (Розробка родовищ, 2017)
Purpose. To rate the main factors and indicators of the national economic security, in particular the degree of the country’s provision with primary natural resources which determine the global energy consumption trends. Findings. Emergencies are ranked in the descending order of optimal flows in the normal mode, the sorting sequence is defined, which results in the optimal solution via a minimum number of the algorithm computational steps. Originality. A universal algorithm for the development of fuel and energy complex of Ukraine has been designed. Цель. Оценить главные факторы и индикаторы национальной экономической безопасности, в частности степени обеспеченности страны основными природными ресурсами, обуславливающими тенденции мирового энергопотребления. Результаты. Проранжированы аварийные ситуации в порядке убывания величины оптимальных потоков в нормальном режиме, определена последовательность перебора, что приводит за минимальное число шагов вычислительного алгоритма к оптимальному решению. Научная новизна. Разработан универсальный алгоритм развития топливно-энергетического комплекса Украины. The authors express their gratitude to Laureate of National Prize of Ukraine, Doctor of Technical Sciences, Professor, Head of the Underground Mining Department, Volodymyr Bondarenko for his guidance while performing work on this topic. Мета. Оцінити головні чинники та індикатори національної економічної безпеки, зокрема ступеня забезпеченості країни основними природними ресурсами, які зумовлюють тенденції світового енергоспоживання. Результати. Проранжовані аварійні ситуації у порядку зменшення величини оптимальних потоків у нормальному режимі, визначено послідовність перебору, що призводить за мінімальне число кроків обчислювального алгоритму до оптимального рішення. Наукова новизна. Розроблено універсальний алгоритм розвитку паливно-енергетичного комплексу України.